Kontribusi Jumlah Pengunjung Obyek Wisata Dataran Tinggi Dieng Bagi Pendapatan Asli Daerah Kabupaten Wonosobo - Andryan Setyadharma; Adi Kurniawan Sujatmiko (JFRES Journal of Fiscal and Regional Economy Studies, 2019)
increasing regional revenue. For a region with limited potential of its’ natural resources it will be a challenge in an attempt to maximize the potential of the region. One of the effort to maximize the regional revenue is by optimizing potential in the tourism sector. Types of data in this research are secondary data such as tourist numbers, consumer price index, General Allocation Grant, and Local Revenue of Wonosobo Regency. The analytical tool is multiple regression analysis with statistical tests and classical assumption. This research aimed to understand the effect of the number of visits tourist, consumer price index, and General Allocation Grant against the Local Revenue of Wonosobo Regency from 2015 to 2017. The results of the regression processing of short-term models show that the consumer price index variable has a significant effect on Regional Original Income with a probability value of 0.0090 smaller than the real level α = 5%. While the variable number of visitors and General Allocation Funds did not have a significant effect on Regional Original Income with a probability value greater than the real level α = 5%.